LABOR PRODUCTIVITY RATING MODEL FOR LIGHT BRICK WALL INSTALLATION IN RESIDENTIAL PROJECTS - Paikun, Paikun; Fatimah, Cici; Nugroho, Nadhya Susilo; Kusmana, Dody (ASTONJADRO, 2021)
Management on a construction project is something that cannot be ignored, because without construction management a project will be difficult to run according to expectations in the form of cost, time, quality and the success or failure of a construction project depends on the effectiveness of resource management. One way that can be done to achieve project objectives is to increase work productivity. This study aims to determine the productivity of labor in the installation of lightweight brick walls based on facts in housing projects. Labor productivity by analyzing the LUR value and productivity rating then becomes the regression analysis data to produce the model. The data search was carried out by direct observation to the field and conducting unstructured interviews with workers in the field. The resource persons are workers as artisans and workers who are experts in the work of installing light brick walls. This productivity measurement uses the productivity rating method, where worker activities are classified into 3 things, namely Essential contributory work, Effective work, and not useful. The results of the analysis show that the productivity of light brick wall installation workers based on the fact has higher productivity than the SNI labor coefficient. To calculate the labor productivity of installing lightweight brick walls, then the model from the results of this study can be used. The results of the evaluation of the model to predict labor productivity for installing lightweight brick walls have an average accuracy of 99.34%, so the model can be declared accurate.